A strategy for realizing tunable luminescence and full-color emission in Sr3Gd2(Si3O9)2:Eu phosphors by introducing dual functional Mn2+. Issue 10 (3rd September 2018) - Zhu, Yingli; Liang, Yujun; Liu, Shiqi; Li, Haoran; Chen, Jiahui; Lei, Wen
Abstract : The introduced Mn 2+ ion can act as both an activator and a structure regulator in the SGSO:Eu system to achieve full-color emission and tunable luminescence of SGSO:0.03Eu, Mn phosphors. Abstract : The exploration of new single-phase phosphors with tunable luminescence and full-color emission is of great importance due to their unique material properties and potential applications in the solid-state lighting field. By introducing Mn 2+ into the SGSO:Eu system, on the one hand, the Mn 2+ ion can act as an activator to emit green light together with the blue light corresponding to Eu 2+ and the red light of Eu 3+ due to the efficient energy transfer from Eu 2+ and Gd 3+ to Mn 2+ and on the other hand, Mn 2+ can also act as a structure regulator to tune the luminescence properties of Eu 2+ and Eu 3+ ions in the SGSO host by varying their site occupation, distribution and polyhedron distortions. As a result, the color hue of SGSO:Eu, Mn can be tuned from cyan to white and to yellow under the excitation of selective ultraviolet (UV) light. A white light-emitting diode (LED) device has been demonstrated by integrating the representative SGSO:Eu, 0.09Mn with a UV LED light source, which shows a low corresponding color temperature (CCT = 4934 K), a high color rendering index ( R a = 86.6), and a CIE color coordinate (0.35, 0.34). In addition, at low Mn 2+ concentrations, the as-prepared SGSO:Eu, Mn presents excellent thermal stability and a tiny chromaticity shift under the excitation of 274 nm light in the temperature range of 298–478 K due to the comparable thermal stability of Eu 2+, Mn 2+ and Eu 3+, while at high Mn 2+ concentrations, the SGSO:Eu, Mn shows a high temperature sensitivity (as high as 2.9% K −1 at 298 K) excited at 350 nm due to the increased thermal stability of Eu 2+ and the decreased thermal stability of Mn 2+ . More importantly, the approach to achieve tunable luminescence and full-color emission via incorporating the activator and structure regulator Mn 2+ ions demonstrated in this work is not limited to the SGSO:Eu material, but applies to other phosphor material systems.